Prefilters on Neutrosophic Sets - D. Keerthana; V. Visalakshi; C. Rajapandiyan; Saeid Jafari (Neutrosophic Sets and Systems)
This paper introduces the concept of a prefilter on the collection of neutrosophic sets. The characteristic set and characteristic value of prefilters are introduced and their fundamental properties are explored. The relationships between filters and prefilters are examined, with particular emphasis on how ultrafilters correspond to maximal filters via specific mappings such as iK and wK Additionally, the concept of prime prefilters are defined and their basic properties are studied. The compatibility between filters and prefilters is also discussed.